Distribution in Saturn's Inner Magnetosphere From 2.4 to 10 RS: A Diffusive Equilibrium Model. Issue 3 (24th March 2020) - Persoon, A. M.; Kurth, W. S.; Gurnett, D. A.; Faden, J. B.; Groene, J. B.; Morooka, M. W.; Wahlund, J. E.; Wilson, R. J.; Menietti, J. D.
Abstract: Electron density measurements have been obtained by the Cassini Radio and Plasma Wave Science (RPWS) instrument covering the period from 30 June 2004 to 19 April 2017, spanning latitudes up to 30° and L values from 2.4 to 10. Near the F ring, electron densities are derived from RPWS measurements of electron plasma oscillations at high latitudes and from the Langmuir Probe (RPWS/LP) sweep data at low latitudes. The electron density measurements from the ring‐grazing orbits, beginning in December 2016, have made it possible to extend the work of a previous diffusive equilibrium model to include the distribution of the ring plasma. Beyond the ring‐grazing orbits, the densities are derived from RPWS measurements of the upper hybrid resonance frequency. These density measurements are used to anchor the fit of an expanded diffusive equilibrium density model for a two‐species plasma consisting of water group and hydrogen ions in Saturn's inner magnetosphere. Density contour plots for the two ion species and the electrons are presented. The distribution of the derived plasma densities is consistent with two primary sources, the Enceladus plume and the extended ring atmosphere. There is also an indication of a weaker plasma source at Dione. In the region just outside the A ring and in the region including the Enceladus orbit, the diffusive equilibrium model also shows the expansion of lighter ions and electrons to higher latitudes along the magnetic field lines with evidence of a weaker plasma expansion between the orbits of Tethys and Dione. Key Point: The diffusive equilibrium density model provides a global map of a two‐species plasma distribution in Saturn's inner magnetosphere